INTENTION TO SERVE “THE SACROSANCT TRUTH” IN THE EXPERIENCE OF THE THINKER LONE WOLDEMAR SCHMIDT (Филологический класс, 2019)
The study focuses on the creative heritage of Woldemar Schmidt, an extraordinary thinker from Siberian province. He experienced a ‘double exile’ to the social periphery, a life-path not untypical for Soviet citizens: his father, being an enemy of the revolution, was executed by firing squad of the Bolsheviks in summer 1921, therefore, living in the back of beyond and isolation was in store for Woldemar. He managed to survive hunger and years of repression, lived through collectivization program, the World War Two, deportation to Siberia, forced labor in NKVD labor columns and years of living in a settlement of internally displaced persons. Woldemar witnessed the collapse of USSR and the change in political ideologies, and he passed away in 2011 in Ishim (Tyumen region). The main feature of his personal history, setting him apart from other Soviet citizens who got the same fate, is the archive of ego-documents. These ego-documents are notable for containing the particular intention to serve truth, which converted an atheist into a believer in God, an aluminum factory worker into a writer, a thinker and even a poet. And it is important to mention that, although Woldemar Schmidt advocated socialism as the most equitable form of social organization, a common renunciation of faith in God seemed to him as a grave mistake. The study defines the main factors have influenced a person, who devoted his life to the idea of salvation of society, through the analysis of social and cultural conditions, survival mechanisms in the terms of isolation and lack of freedom, and the writer’s strategies and intentions.